2010
DOI: 10.1167/iovs.09-4523
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Cathepsins and Obesity-Induced Proinflammatory Cytokines in Lacrimal Glands of Male NOD Mouse

Abstract: Expression of CATS and CATH increases in parallel with proinflammatory cytokines during the development of autoimmune inflammatory disease in the NOD mouse disease model. Tear CATS may represent a biomarker for diagnosis of dacryoadenitis in SjS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 46 publications
8
84
1
1
Order By: Relevance
“…CTSH overexpression typically correlates to macrophage infiltration and a proinflammatory environment in a number of tissues 58, 59. Therefore it is likely that the loss of Ctsh leads to an increase in levels of other cathepsins, such as our observation of increased levels of cathepsin B, which might have a proinflammatory role and is known to play an important role in processing of mast cell proteases 60, 61.…”
Section: Discussionmentioning
confidence: 79%
“…CTSH overexpression typically correlates to macrophage infiltration and a proinflammatory environment in a number of tissues 58, 59. Therefore it is likely that the loss of Ctsh leads to an increase in levels of other cathepsins, such as our observation of increased levels of cathepsin B, which might have a proinflammatory role and is known to play an important role in processing of mast cell proteases 60, 61.…”
Section: Discussionmentioning
confidence: 79%
“…The study revealed an increased level of cathepsin S at the mRNA level, as well as increased levels of protein as determined by immunofluorescence and activity (Li et al, 2010). In a separate study, deletion of cathepsin S in mice was shown to significantly attenuate the onset of diabetes, thus providing a level of protection (Hsing et al, 2010).…”
Section: Diabetes and Obesitymentioning
confidence: 87%
“…In an earlier study with the non-obese diabetic (NOD) mouse, a well-established murine model for SS, we demonstrated increased cathepsin S (Ctss) expression and activity in LG acinar cells that was paralleled by elevated tear Ctss activity as compared to control mice (16). Similarly, Ctss gene expression is up-regulated in the early stages of disease and, in contrast to other cathepsins, remains up-regulated throughout the later stages of disease in the C57BL/6.NOD-Aec1Aec2 mouse model of SS (17).…”
Section: Introductionmentioning
confidence: 97%